Genotypic diversity in clinical and environmental isolates of Cryptococcus neoformans from India using multilocus microsatellite and multilocus sequence typing. Issue 3 (13th January 2020) - Prakash, Anupam; Sundar, Gandhi; Sharma, Brijesh; Hagen, Ferry; Meis, Jacques F.; Chowdhary, Anuradha
Summary: Background: Cryptococcus neoformans is the leading cause of cryptococcal meningitis in HIV/AIDS patients. As infections in humans are predominantly caused by the inhalation of basidiospores from environmental sources, therefore, analysing the population structure of both clinical and environmental populations of C neoformans can increase our understanding of the molecular epidemiology of cryptococcosis. Objective: To investigate the genotypic diversity and antifungal susceptibility profile of a large collection of C neoformans isolates (n = 523) from clinical and environmental sources in India between 2001 and 2014. Materials and methods: Cryptococcus neoformans isolates were genotyped by AFLP, microsatellite typing (MLMT) and MLST. In vitro antifungal susceptibility for standard antifungals was undertaken using CLSI M27‐A3. Results: All isolates were C neoformans, AFLP1/VNI and exhibited mating‐type MATα. MLMT revealed that the majority of isolates belonged to microsatellite cluster (MC) MC3 (49%), followed by MC1 (35%), and the remaining isolates fell in 11 other MC types. Interestingly, two‐thirds of clinical isolates were genotype MC3 and only 17% of them were MC1, whereas majority of environmental strains were MC1 (54%) followed by MC3 (16%). Overall, MLST assigned 5 sequence types (STs) among all isolates and ST93 was the most common (n = 76.7%), which was equally distributed in both HIV‐positive and HIV‐negative patients. Geometric mean MICs revealed that isolates in MC1 were significantly less ( P < .05) susceptible to amphotericin B, 5‐flucytosine, itraconazole, posaconazole and isavuconazole than isolates in MC3. Conclusions: The study shows a good correlation between MLMT and MLST genotyping methods. Further, environmental isolates were genetically more diverse than clinical isolates.